MANAGEMENT OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS PRESENTING WITH ST-SEGMENT ELEVATION - F. Van de Werf; D. Ardissino; A. Betriu; D. Cokkinos; E. Falk; K. Fox; D. Julian; M. Lengyel; F.J. Neumann; W. Ruzyllo; C. Thygesen; R. Underwood; et al. (Рациональная фармакотерапия в кардиологии, 2015)
The Task Force on the Management of Acute Myocardial Infarction of the European Society of Cardiology.